The labour share of income: Heterogeneous causes for parallel movements? - Jan Hogrefe; Marcus Kappler (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2010)
The aim of this paper is to take a structured approach at estimating the coefficients of factors explaining movements of the labour share across countries. In particular, we focus on proper dynamic specification and test the validity of the homogeneity assumption of slope coefficients frequently implied in previous studies. We employ fixed effect estimators as well as pooled mean group and mean group estimators, the latter in a dynamic heterogeneous panel framework. We find support for a dynamic estimation setup and derive statements regarding the homogeneity assumption with respect to the three most prominent explanatory variables in the literature: the capital-output ratio, total factor productivity and trade openness. In addition, we take account of different institutional arrangements across countries.
Keywords: C23; E23; E25; F16; 330; factor income; labour share; dynamic heterogeneous panel models; Lohnquote; Panel; Schätzung; Kapitalintensität; Produktivität; Außenhandelsliberalisierung; Welt